2003
DOI: 10.1046/j.0001-6772.2003.01186.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptor β is expressed in adult human skeletal muscle both at the mRNA and protein level

Abstract: The present study shows for the first time ERbeta mRNA and protein expression in human skeletal muscle tissue in both males and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 43 publications
6
94
2
1
Order By: Relevance
“…7 Estrogens also act through cell membrane located receptors, which can be independent of ESRs. 8 ESRs have been found in human skeletal muscle 9,10 suggesting the contribution of estrogens to muscle functions. Recent experimental animal studies have provided evidence that estrogen, via its receptors, has a role in glucose metabolism in muscle 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Estrogens also act through cell membrane located receptors, which can be independent of ESRs. 8 ESRs have been found in human skeletal muscle 9,10 suggesting the contribution of estrogens to muscle functions. Recent experimental animal studies have provided evidence that estrogen, via its receptors, has a role in glucose metabolism in muscle 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The two ERs show overlapping, yet distinct, patterns of expression (DahlmanWright et al 2006). Of particular relevance for glucose homeostasis, ERa is the major ER expressed in the liver (Kuiper et al 1997), adipose tissue (Lundholm et al 2004), skeletal muscle (Wiik et al 2003), and pancreatic islets (Geisler et al 2002). ER subtype-specific ligands have been developed, and are increasingly used to further clarify the specific roles of ERa and ERb .…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, tendon collagen synthesis is lower in women compared with men at rest and after exercise (47). In addition, a lower peak stress in female collagen fascicles from patella tendons has been demonstrated compared with fascicles from men (41).Estrogen receptors have been localized to bone, ligaments, and muscle tissue (39,56,64), and animal data have shown that tendons express transcripts for estrogen receptors (22). However, the effect of estrogen on collagen synthesis is conflicting, which probably is related to variation between animal species and the applied methods.…”
mentioning
confidence: 99%
“…Estrogen receptors have been localized to bone, ligaments, and muscle tissue (39,56,64), and animal data have shown that tendons express transcripts for estrogen receptors (22). However, the effect of estrogen on collagen synthesis is conflicting, which probably is related to variation between animal species and the applied methods.…”
mentioning
confidence: 99%